Al Attiya v. Al Thani. (2018) - Unknown
Abstract : State immunity — Jurisdictional immunity — Officials — Whether State immunity bar to jurisdiction — State Immunity Act 1978 — Claim for damages relating to abuse of power by State official — Whether State indirectly impleaded Diplomatic relations — Immunity — Diplomatic agent — Diplomatic Privileges Act 1964 — Whether diplomatic agent entitled to immunity — Vienna Convention on Diplomatic Relations, 1961, Articles 31(1) and 42 — Whether entitlement to immunity for private commercial activity — The law of England